Formative Assessment on Science Learning to Improve the Quality of Learning in Curriculum Merdeka - Jenny I S Poerwanti; Sri Marmoah; Supianto; Sukarno; Hasan Mahfud; Siti Istiyati (Postgraduate, University of Mataram, 2024)
Formative assessment is a learning assessment whose target is formative and aims to evaluate the learning process. In reality, there are still many teachers who have not implemented formative assessment optimally in science learning. Formative assessments conducted in the middle, end, or throughout learning aim to determine student progress while providing quick feedback to teachers, for example regarding student understanding of the material. This study aims to find out the things that educators need to prepare and how they carry it out. The research method used a descriptive method with a qualitative approach, through distributing questionnaires and interviews. The target respondents were elementary school teachers who teach grade VI students. The data that has been collected is then processed using a Likert scale. The results showed that what needs to be prepared by teachers to conduct formative assessment in science subjects is a clear understanding of concepts, and prepare the three stages of formative assessment carefully. Based on the results of the questionnaire, teachers are still not optimal in the information-gathering and action-taking stages. Ways that can be done to implement formative assessment in improving the quality of learning, can be started from the preparation of the right learning module.